ASSOCIATION OF ATM GENETIC VARIANT (rs3092856) POLYMORPHISM WITH BREAST CANCER IN KHYBER PAKHTUNKHWA (The Research of Medical Science Review, 2024)
Currently, breast cancer is a major health concern among the women population. It is caused by the abnormal proliferation of cells inside the breast resulting in the formation of lumps, which can metastasize to other areas in the body. Annually, there are almost a million females diagnosed with breast cancer worldwide. In most cases breast cancer results from some mutations of a few genes such as Ataxia telangiectasia Mutated (ATM), which is found to be over-expressed in nearly 50% of breast cancers. In this study, we obtained a total of 334 blood samples from Khyber Pakhtunkhwa, out of which 184 were past Breast cancer symptomatic while 150 were healthy controls. In this way, we obtained pure blood from diseased and healthy individuals using the Phenol-Chloroform method to extract DNA from whole blood. Similarly, genotyping was done using Allele-Specific PCR (ASPCR) by utilizing specially designed tetra primers for each allele and statistical analysis was done using IBM SPSS software. The amplification product was localized on 2% agarose gel using a UV illuminator. The polymorphism distribution of the ATM Genetic variant rs3092856 in breast cancer patients and healthy controls indicates the SNP (rs3092856) has a significant (P=0.0079, χ2=8.970,2) role in breast cancer protective mechanism in Khyber Pakhtunkhwa. Besides, the heterozygous dominant genotypes in patients with breast cancer and the CC genotypes in homozygous dominant genotypes had statistically higher prevalence compared to healthy controls. However, patients with breast cancer had significantly less frequency of homozygous recessive Genotype (GG) than healthy controls. Additionally, we noted that the cases had a similar low frequency of the minor allele (G) compared to the controls, which showed the same trend of associations. The above-mentioned findings infer that the risk associated with developing breast cancer is associated with the C allele while the G allele exerts a strong protective effect in the Khyber Pakhtunkhwa population afflicted with breast cancer.